Paciente masculino de 47 años de edad con tumor maligno de estómago. - Romero Barros, Mayerly Jhoannye (2021)
This clinical case focuses on a 47-year-old patient, with a number of complications, preventing a quiet life, he refers a personal pathological history of chronic gastritis 7 months ago, receiving this assessment from the doctor in charge of treating him, the patient refers that from that time on, he has presented discomfort more frequently, an intervention is carried out where the doctor notices the presence of a mass in the stomach where it causes pain and discomfort. The family doctor in charge performs an intervention of physical examinations and orders the complementary tests to give an accurate diagnosis, the patient does not refer to allergies or a history of surgeries, a palpation is performed where he finds the novelty of presenting pulsatile abdominal pain showing a Mild to moderate intensity in the epigastric picture, presents symptoms of nausea, dyspepsia, weight loss and lower digestive bleeding, shows a pale skin. A physical examination is performed in the head area with a normal skull and hair of normal implantation, its mucous membranes are moist and pale, neck there is no jugular engorgement or adenopathy, an auscultation is performed where there are air-fluid noises, at the soft depressible and painful palpation of pulsatile type of mild to moderate intensity at the regional epigastrium level without irradiation, presence of a solid mass with irregular border, negative upper middle and lower urethral points, negative percussion fists, no edema, complementary examinations show the result moderate anemia and lower digestive bleeding, an upper digestive endoscopy was performed with results of an infiltrative stomach tumor. Patient is sent to an outpatient clinic to take better care in the area of nutrition and thus acquire a better nutritional status, through a nutritional plan and corresponding monitoring, in order to have a better body composition and gain necessary weight of 14 kilograms and in turn improve the symptoms of malignant stomach tumor.